Traveling Wave Magnetic Particle Imaging for determining the iron-distribution in rock - Vogel, Patrick; Rückert, Martin Andreas; Klauer, Peter; Kullmann, Walter H.; Jakob, Peter Michael; Behr, Volker Christian (Diffusion Fundamentals, 2014)
Determining the composition of solid materials is of high interest in areas such as material research or quality assurance. There are several modalities at disposal with which various parameters of the material can be observed, but of those only magnetic resonance imaging (MRI) or computer tomography (CT) offer anon-destructive determination of material distribution in 3D. A novel non-destructive imaging method is Magnetic Particle Imaging (MPI), which uses dynamic magnetic fields for a direct determination of the distribution of magnetic materials in 3D. With this approach, it is possible to determine and differentiate magnetic and non-magnetic behaviour. In this paper, the first proof-of-principle measurements of magnetic properties in solid environments are presented using a home-built traveling wave magnetic particle imaging scanner.